(3ebGdI LhGH aj HQgGf eSFdI eVGaI Edi GdebGdI GdSGHYI ef cJGH EbdjOSs - (3CHh GdaJhM fLe GdOjf CMeO Hf eMeO Hf GdSQj GdHZOGOj, GHf GdUdGM,J (B548 (3g` s
(3ChdgG (B:s
(3bGd ageJ CSYOc Gddg eG bdJg ai GdTcd GdQGHY YTQ ef GdebGdI GdSGHYI ef cJGH GdCUhd hgh GdTcd GdPi jHjf ajg CbdjOS Cf GdCYOGO ai efJgi GdeSGhGI s
(3BNQgG (B:s
(3aVdkG Yf Cf jSJYed ajg fSHI GdeSGhGg GdeVWQHg aLGR Cf jDNQ YfgG dGf JbOe fSHI GdeSGhGI Ydi gPg GdCTcGd djS JbOe VQhQi HgG JbOe HGdhVY Je Gdbhd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdJGSYs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs